Separator and electrochemical device including the same
The separator for lithium secondary batteries, featuring a porous substrate with an inorganic particle layer containing metal silicate and a limited organic compound content, addresses the challenges of heat resistance and adhesion at thin thicknesses, enhancing the performance and safety of electrochemical devices.
Patent Information
- Application Number
- JP2024160847
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-01
AI Technical Summary
Existing separators for lithium secondary batteries face challenges in achieving high mechanical strength, heat resistance, and transmittance while maintaining safety, especially at thinner thicknesses, which is crucial for high capacity and high output batteries.
A separator comprising a porous substrate with an inorganic particle layer on one or both sides, where the inorganic particle layer contains inorganic particles, a metal silicate as the inorganic binder, and an organic compound with a content below that of the inorganic binder, enhancing heat resistance and adhesion.
The proposed separator achieves excellent heat resistance and adhesion even at thin thicknesses, reducing heat shrinkage and improving the overall performance and safety of electrochemical devices.
Smart Images

Figure 2025044173000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a separator and an electrochemical device including the same. [Background technology]
[0002] In recent years, in line with the trend toward high capacity and high output of secondary batteries, there is an increasing demand for improved separator properties, such as high strength, high transmittance, thermal stability, and electrical safety of secondary batteries during charging and discharging. In the case of separators for lithium secondary batteries, high mechanical strength is required to improve safety during the manufacturing process and use of the battery, and high transmittance and high thermal stability are required to improve capacity and output.
[0003] Meanwhile, research is being conducted to make the separator thinner in order to achieve high capacity and high output characteristics of electrochemical devices, but when the separator is made thinner, there is a problem that the mechanical strength and / or heat resistance is reduced. When the mechanical strength and / or heat resistance is reduced, there is a high possibility that safety problems will occur during the manufacturing process and during use of the battery. For example, a short circuit may occur between the electrodes due to damage or deformation of the separator caused by an increase in temperature inside the battery, which may increase the risk of overheating or fire of the battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Korean Patent Publication No. 2016-0109669 (2016.09.21) Summary of the Invention [Problem to be solved by the invention]
[0005] According to one embodiment of the present disclosure, it is possible to provide a separator that has excellent heat resistance even when it is thin, and an electrochemical device including the separator. According to another aspect of the present disclosure, it is possible to provide a separator having improved adhesion and transmittance even with a thin thickness, and an electrochemical device including the separator. According to still another aspect of the present disclosure, an electrochemical device having excellent performance can be provided.
[0006] The separator of the present disclosure can be widely applied to environmental technology fields such as electric vehicles, battery charging stations, solar power generation using other batteries, wind power generation, etc. In addition, the separator of the present disclosure can be used in eco-friendly electric vehicles, hybrid vehicles, etc., which suppress air pollution and greenhouse gas emissions to prevent climate change. [Means for solving the problem]
[0007] The separator according to the present disclosure includes a porous substrate and an inorganic particle layer located on one or both sides of the porous substrate, the inorganic particle layer including inorganic particles and an inorganic binder, the inorganic particle layer including an organic compound in an amount less than the content of the inorganic binder, and the inorganic binder including a metal silicate.
[0008] In one embodiment, the metal silicate may connect and fix the inorganic particles together and between the inorganic particle layer and the porous substrate. In one embodiment, the organic compound may include one or more first organic compounds selected from the group consisting of polycarboxylates, sulfonates, and polysiloxane-based compounds, one or more second organic compounds selected from the group consisting of ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers, and fluorine-based polymers, or a combination thereof.
[0009] In one embodiment, the organic compound may comprise less than 30% by weight of a second organic compound, based on the total weight of the organic compound. In one embodiment, the organic compound may not include a second organic compound.
[0010] In one embodiment, the metal of the metal silicate may be any one or more metals selected from the group consisting of Group 1, Group 2, and Group 13 metals.
[0011] In one embodiment, the metal of the metal silicate may be any one or more metals selected from the group consisting of Group 1 and Group 2 metals. In one embodiment, the metal silicate may be represented by Formula 1 below:
[0012] [Chemical formula 1] M2O·nSiO2 In the above formula 1, M is an alkali metal, and n is 4-10.
[0013] In one embodiment, the inorganic particles may include any one or more selected from the group consisting of metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates.
[0014] In one embodiment, the inorganic particles may have an average particle size (D50) of 1 μm or less. In one embodiment, the total thickness of the inorganic particle layer formed on the porous substrate may be 5 μm or less.
[0015] In one embodiment, the separator may have a thermal shrinkage rate of 3% or less in the width direction measured after being left at 130° C. for 60 minutes. In one embodiment, the separator may have a thermal shrinkage rate of 7% or less in the width direction measured after being left at 150° C. for 60 minutes.
[0016] In one embodiment, the inorganic particle layer may contain 0.1 to 20 parts by weight of a metal silicate with respect to 100 parts by weight of the inorganic particles. In one embodiment, the porous substrate may include polar groups on the surface. The electrochemical device according to the present disclosure may include a separator as described above. Effect of the Invention
[0017] The separator according to the present disclosure can have excellent heat resistance even when it is thin, and therefore can have a very low thermal shrinkage rate even when it is thin. Furthermore, the separator according to the present disclosure can have excellent adhesion and transmittance even with a small thickness. Moreover, the present disclosure can provide an electrochemical device having excellent performance by including a separator according to an embodiment. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic cross-sectional view of a separator according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present disclosure will now be described in detail, by way of example only, and is not intended to be limited to the specific embodiments illustratively described. Additionally, as used in the specification and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0020] In addition, the numerical ranges used herein include the lower limit and the upper limit, all values within the range, increments logically derived from the form and width of the ranges defined, all values limited therein, and all possible combinations of upper and lower limits of numerical ranges limited in different forms. Unless otherwise specified herein, values outside the numerical ranges that may occur due to experimental error or rounding of values are included in the defined numerical ranges.
[0021] Furthermore, throughout the specification, "comprising" an element means that it may further include other elements, but not to the exclusion of other elements, unless specifically stated to the contrary.
[0022] As used herein, when a layer, film, region, plate or other part is said to be "on" or "above" another part, this includes not only when it is "directly on" the other part, but also when there is another part between them.
[0023] In this specification, the term "average particle size" refers to "D50", which means the particle size of inorganic particles equivalent to 50% of the total volume fraction. The average particle size can be derived from the particle size distribution results obtained by taking samples of inorganic particles to be measured according to ISO 13320-1 standard and analyzing them using S3500 manufactured by MICROTRAC.
[0024] Fig. 1 is a schematic cross-sectional view of a separator according to an embodiment. Referring to Fig. 1, the present disclosure provides a separator comprising a porous substrate and an inorganic particle layer located on one or both sides of the porous substrate, the inorganic particle layer comprising inorganic particles and an inorganic binder, the inorganic particle layer comprising an organic compound less than the content of the inorganic binder, and the inorganic binder comprising a metal silicate.
[0025] As a measure to ensure the safety of batteries, a composite separator has been developed in which a porous inorganic particle layer is formed in a porous substrate, the inorganic particles being connected to each other by the organic binder and bonded to the porous substrate by the organic binder, and a polymer-based organic binder is included in the porous substrate.
[0026] However, such organic / inorganic composite separators have a problem that when a thin inorganic particle layer below a certain thickness is formed, the heat shrinkage rate at high temperatures decreases, making it practically impossible to make the separator thinner, and limiting its suitability for high-capacity / high-power batteries.
[0027] Meanwhile, when an organic binder is used, a relatively large amount of the organic binder is used above a certain content in order to have sufficient adhesive strength. As a result, a chemical reaction occurs between the electrolyte of the battery and the organic binder component, which causes deformation of the binder component, or the reaction generates gas, and the gas leaks due to heat, resulting in a decrease in the life of the battery. In addition, there are various problems that decrease the performance of the battery, such as the excessive organic binder dissolving and eluting in the electrolyte, the organic binder swelling due to the electrolyte closing the pore layer, or increasing the volume of the battery. It has been confirmed that such problems caused by the organic binder become more serious when a thin inorganic particle layer is formed.
[0028] Therefore, the inventors of the present disclosure have conducted continuous research to provide a separator that has excellent heat resistance even at a thinner thickness and that solves the problems of the organic / inorganic composite separator described above. As a result, they have confirmed that by forming an inorganic particle layer that contains an inorganic binder containing a metal silicate and an organic compound in an amount less than that of the inorganic binder, a separator that has excellent heat resistance and adhesiveness even at a thinner thickness and has excellent transmittance can be provided.
[0029] In one embodiment, the metal silicate may connect and fix the inorganic particles and the inorganic particle layer to the porous substrate. It is believed that the separator can exhibit high adhesion by connecting or anchoring the inorganic particles and / or the inorganic particle layer to the porous substrate through the metal silicate.
[0030] In the separator according to an embodiment, inorganic particles may be connected to each other by a metal silicate to form pores. That is, the inorganic particle layer may include inorganic particles and an inorganic binder, or may be a porous inorganic particle layer in which inorganic particles are connected and fixed by the inorganic binder to form pores.
[0031] In one embodiment, the surface and / or pores of the porous substrate may be coated with a metal silicate. This allows the adhesive strength between the inorganic particle layer and the surface of the porous substrate to be excellent. This is believed to be because the metal silicate not only connects and fixes the inorganic particles to each other, but also penetrates and anchors the inorganic particles into the pores formed in the porous substrate, thereby providing a strong adhesive effect to the porous substrate.
[0032] In one embodiment, the inorganic particle layer may be formed on one or both sides of the porous substrate, covering 90% or more of the total area of each side, specifically 95% or more, and more specifically, 100% of the total area of each side of the porous substrate, except in cases where minute defects occur, and the inorganic particle layer is formed by inorganic particles adjacent to each other and pores being formed between the inorganic particles.
[0033] In one embodiment, the organic compound may refer to an additive used in the manufacture of a separator as known in the art. Examples of the additive include organic compounds including an organic binder, a dispersant, a wetting agent, a lubricant, an antifoaming agent, or a thickener. Specifically, the organic compound may include at least one selected from a dispersant that prevents aggregation of inorganic particles in a coating slurry used in forming an inorganic particle layer, a wetting agent that improves the coating properties of the slurry, and an organic binder that improves adhesion between inorganic particles and / or between the inorganic particle layer and the porous substrate.
[0034] The separator according to the embodiment uses an inorganic binder containing a metal silicate and uses an organic compound containing an organic binder in a significantly smaller amount than in the past, thereby realizing excellent heat shrinkage characteristics at a thin thickness that could not be realized by a separator using an excessive amount of an organic compound containing an organic binder. This makes it possible to prevent ignition or explosion due to abnormal phenomena such as a sudden temperature rise, and enables the separator for secondary batteries to be thin, making it suitable for application to high-capacity / high-output batteries. In addition, the separator according to the embodiment has excellent binding strength between particles contained in the inorganic particle layer and adhesive strength between the porous substrate and the inorganic particle layer.
[0035] In the separator according to one embodiment, the inorganic particle layer contains a metal silicate as an inorganic binder, and therefore problems such as pore blockage and expansion caused by organic compounds such as polymer-based organic binders do not occur, and the separator has excellent ion migration, and there is no hindrance to the migration of ions such as lithium ions, and the electrical characteristics such as the capacity and efficiency of the battery can be significantly improved.
[0036] In one embodiment, the organic compound may include one or more first organic compounds selected from the group consisting of polycarboxylates, sulfonates, and polysiloxane-based compounds, one or more second organic compounds selected from the group consisting of ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers, and fluorine-based polymers, or a combination thereof, but the organic compound may be substituted with other components without departing from the scope of the present disclosure.
[0037] In one embodiment, the first organic compound may be an additive other than a binder. In this case, the additive other than a binder may be any one or more of a dispersant, a wetting agent, a lubricant, an antifoaming agent, and a thickener, but is not limited thereto, and may be an additive that can be generally contained in an inorganic particle layer. In addition, the dispersant may be one that prevents aggregation of inorganic particles in a coating slurry used when forming an inorganic particle layer, and the wetting agent may be one that improves the coating property of the slurry.
[0038] In one embodiment, the second organic compound may be an organic binder, and the organic binder may connect and fix inorganic particles together and between the inorganic particle layer and the porous substrate.
[0039] The polycarboxylate may be any one or more selected from, but not limited to, sodium polyacrylate, ammonium polyacrylate, etc. The sulfonate may be any one or more selected from, but not limited to, dialkyl sulfosuccinate salt, alkyl diphenyl ether disulfonate salt, alkyl benzene sulfonate salt, etc. The polysiloxane compound may be any one or more selected from, but not limited to, 3-(polyethylene)propylheptamethyltrisiloxane, 3-(3-hydroxypropyl)-heptamethyltrisiloxane ethoxylated acetate, methyl(propyl hydroxide)(ethoxylated)bis(triethylsiloxy)silane, etc.
[0040] The ester-based polymer may be any one or more selected from polyethylene terephthalate, polyethylene naphthalate (PEN), and the like. The amide-based polymer may be any one or more selected from polyamide-6, polyamide-66, and the like. The imide-based polymer may be any one or more selected from polyimide, polyetherimide, polyesterimide, and the like. The acrylic-based polymer may be any one or more selected from polyacrylamide, polymethacrylate, polyethyl acrylate, polyacrylate, polybutyl acrylate, and acrylic acid-methacrylic acid copolymer, and the like. The styrene-based polymer may be any one or more selected from polystyrene, poly-α-methylstyrene, and polybromostyrene, and the like. The vinyl alcohol-based polymer may be any one or more selected from polyvinyl alcohol, polyvinyl acetate, and polyvinyl acetate-polyvinyl alcohol copolymer, and the like. The vinylpyrrolidone-based polymer may be any one or more selected from polyvinylpyrrolidone, copolymers containing vinylpyrrolidone, and the like. The cellulose-based polymer may be any one or more selected from carboxylmethylcellulose, cellulose acetate propionate, cellulose acetate, cellulose acetate butyrate, etc. The fluorine-based polymer may be any one or more selected from polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyhexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene, polychlorotrifluoroethylene, etc.
[0041] In one embodiment, the organic compound may contain less than 30% by weight of the second organic compound based on the total weight of the organic compound, specifically less than 20% by weight, less than 10% by weight, or less than 5% by weight of the second organic compound. When the second organic compound is contained in the above-mentioned range, problems such as pore blockage and expansion due to the second organic compound do not occur, and the separator has excellent ion migration, is not hindered in the migration of ions such as lithium ions, and has significantly improved electrical properties such as battery capacity and efficiency.
[0042] In one specific example, the organic compound may not include a second organic compound. The separator according to one embodiment includes a metal silicate as an inorganic binder, and therefore has excellent heat resistance and adhesiveness even when thin, even without including a second organic compound that can be used as an organic binder, and can more effectively suppress the problem of battery performance degradation.
[0043] In one embodiment, the content of the organic compound is not particularly limited as long as it is less than the content of the inorganic binder. For example, the inorganic particle layer may contain 0.001 to 15 parts by weight, 0.001 to 13 parts by weight, or 0.001 to 8 parts by weight of the organic compound relative to 100 parts by weight of the inorganic particles. More specifically, the content of the organic compound may be 0.001 to 5 parts by weight, 0.01 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight relative to 100 parts by weight of the inorganic particles.
[0044] In one embodiment, the metal of the metal silicate may be any one or more metals selected from the group consisting of metals of Groups 1, 2, and 13. That is, the metal may be one or more metals selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), and indium (In).
[0045] In one embodiment, from the viewpoint of improving the heat resistance and adhesiveness of the separator, the metal of the metal silicate may be any one or more metals selected from the group consisting of metals of Groups 1 and 2. That is, the metal may be one or more metals selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba). More preferably, the metal of the metal silicate may be one or more alkali metals selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs). In the case of the alkali metal silicate, the thermal shrinkage rate is the lowest compared to other types of metals, and the most excellent heat resistance can be realized.
[0046] In one embodiment, the metal silicate may have a structure containing a metal oxide and silica at a certain molar ratio. Specifically, the molar ratio of the metal oxide and silica may be 1:4 to 1:10, specifically 1:4 to 1:9, more specifically 1:4.5 to 1:8.5, and even more specifically 1:5 to 1:8.
[0047] In one embodiment, the metal silicate may be represented by Formula 1 below:
[0048] [Chemical formula 1] M2O·nSiO2 In the above formula 1, M is an alkali metal, and n is 4-10.
[0049] The metal silicate satisfies Chemical Formula 1, and thus the effect of connecting and fixing between the inorganic particles and between the inorganic particle layer and the porous substrate can be more effectively achieved. As a result, the separator according to an embodiment not only has more excellent binding strength between the inorganic particles and adhesion strength between the porous substrate and the inorganic particle layer, but also has excellent heat shrinkage characteristics even at a thin thickness. In the above Chemical Formula 1, n may be 4-9, 4.5-8.5, or 5-8.
[0050] In one embodiment, the inorganic particles are not limited as long as they are inorganic particles used in the art. As a non-limiting example, the inorganic particles may include any one or more selected from the group consisting of metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates. For example, the inorganic particles may include any one or more selected from the group consisting of magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), alumina (Al2O3), boehmite (γ-AlO(OH)), aluminum hydroxide (Al(OH)3), silica (SiO2), silicon carbide (SiC), calcium oxide (CaO), titanium dioxide (TiO2), strontium titanate (SrTiO3), barium titanate (BaTiO3), barium sulfate (BaSO4), zinc oxide (ZnO), yttrium oxide (Y2O3), zirconium oxide (ZrO2), tin oxide (SnO2), and cerium oxide (CeO2). From the viewpoint of battery stability, the inorganic particles may be any one or more metal hydroxide particles selected from the group consisting of bohemite, aluminum hydroxide (Al(OH)3), and magnesium hydroxide (Mg(OH)2). In one embodiment, the shape of the inorganic particles is not limited and may be spherical, elliptical, acicular, etc.
[0051] In one embodiment, the inorganic particles may have an average particle size (D50) of 1 μm or less, 0.7 μm or less, 0.01 μm or more, 0.05 μm or more, or a value between the above numerical values, specifically, 0.01 to 1 μm, or 0.05 to 0.7 μm. When the average particle size of the inorganic particles satisfies the above-mentioned range, better heat shrinkage properties can be achieved at a thin thickness.
[0052] Preferably, the inorganic particles may have an average particle size (D50) of 0.5 μm or less, specifically 0.35 μm or less. The separator according to one embodiment contains metal silicate and inorganic particles having an average particle size (D50) of 0.5 μm or less or 0.35 μm or less, thereby further improving the thermal shrinkage characteristics at a thin thickness.
[0053] In one embodiment, the inorganic particle layer may be coated on one side or both sides of the porous substrate. When the inorganic particle layer is coated on both sides of the porous substrate, the thicknesses of the inorganic particle layers coated on one side and the other side may be the same or different.
[0054] In one embodiment, the total thickness of the inorganic particle layer formed on the porous substrate may be 5 μm or less, 3 μm or less, 2.5 μm or less, 2 μm or less, 0.1 μm or more, 0.5 μm or more, 1 μm or more, or a value between the above values. Specifically, the total thickness of the inorganic particle layer may be 0.1 to 5 μm, 0.5 to 3 μm, 1 to 2.5 μm, or 1 to 2 μm. However, this means that significantly improved heat resistance and adhesiveness can be achieved even under the thickness ranges described above, so it is not necessarily limited thereto, and the total thickness of the inorganic particle layer can be changed without departing from the scope of the present disclosure.
[0055] The separator according to one embodiment may have excellent heat resistance even when it is thin. In one embodiment, the separator may have a thermal shrinkage rate of 3% or less, preferably 2% or less, and more preferably 1% or less in the width direction measured after being left at 130° C. for 60 minutes.
[0056] In addition, the separator according to one embodiment can have excellent heat shrinkage properties at higher temperatures. In one embodiment, the separator may have a heat shrinkage in the width direction measured after being left at 150° C. for 60 minutes, and may have a heat shrinkage of 7% or less, preferably 5% or less, and more preferably 3% or less.
[0057] In the separator according to one embodiment, the ΔGurley air permeability calculated by the following formula 1 in the Gurley air permeability measured in accordance with ASTM D726 may be 50 sec / 100 cc or less, specifically 40 sec / 100 cc or less, and the lower limit thereof may be, for example, 5 sec / 100 cc.
[0058] [Formula 1] ΔGurley air permeability (sec / 100cc) = Gurley air permeability of separator with inorganic particle layer formed - Gurley air permeability of porous substrate
[0059] In one embodiment, the inorganic particle layer may contain 0.1 to 20 parts by weight, 1 to 15 parts by weight, or 1 to 10 parts by weight of metal silicate relative to 100 parts by weight of inorganic particles, but is not necessarily limited thereto.
[0060] In one embodiment, the porous substrate may include a polar group on the surface. In this case, the polar group may be, but is not limited to, a carboxylic acid group, an aldehyde group, or a hydroxyl group. The separator according to one embodiment includes a porous substrate having a polar group on the surface, and thus can simultaneously achieve excellent heat shrinkage properties and adhesiveness even at a small thickness.
[0061] The polar group may be introduced by a specific surface treatment. Specifically, the surface treatment may be, but is not limited to, a plasma treatment, a corona discharge treatment, or an electron beam treatment in the presence of one or more selected from oxygen, air, and ozone.
[0062] In one embodiment, the porous substrate may be a porous polymer film, sheet, nonwoven fabric, woven fabric, or the like made from a polymer used as a separator, and may include a porous substrate having a laminated structure in which two or more of the above layers are laminated.
[0063] In one embodiment, the porous substrate may be a polyolefin-based porous substrate such as polyethylene, polypropylene, or a copolymer thereof, but is not limited thereto, and any porous substrate known as a porous substrate for a separator of an electrochemical device may be used.
[0064] In one embodiment, the porous substrate may have a porosity of 20 to 60%, specifically, but not limited to, 30 to 60%. The porosity can be calculated by the following formula: Porosity(%)=(1-True Density / Bulk Density)×100 True Density(g / cm 3 )=Mass of CCS(g) / Volume of CCS(cm 3 ) *Volume(cm 3 )=Thickness of CCS(cm)×area of CCS(cm 2 ); CCS=Ceramic coated separator(Porous ceramic+Porous PE) Bulk Density(g / cm 3 )=ρ ceramic ×(m ceramic / m composite )+ρ pe ×(m PE / m composite ) *ρ=Theoretical density of bulk materials; Composite(Non-pouous ceramic+Non-pouous PE)
[0065] In one embodiment, the porous substrate may have a thickness of, but is not limited to, 1 to 25 μm, 3 to 20 μm, or 5 to 15 μm. The thickness can be measured using a Mitutoyo Thickness Gauge.
[0066] In one embodiment, the average thickness of the separator may be, but is not necessarily limited to, 5 to 30 μm, 10 to 25 μm, or 10 to 20 μm. The average thickness can be measured by the following method. Specifically, 10 separator layers are stacked, and the thickness can be measured using a Mitutoyo Thickness Gauge. The thickness is then divided by 10 to obtain the thickness of a single layer. The same procedure can then be repeated for five points in the TD direction to calculate the average value.
[0067] In one embodiment, the inorganic particle layer contains an organic compound less than the content of the inorganic binder, which means that the inorganic particle layer does not contain an organic compound. That is, the inorganic particle layer may be composed of inorganic particles and a metal silicate inorganic binder. Even if the above-mentioned organic compound is not present, the inorganic particle layer is adhered to the porous substrate with excellent adhesive strength, and can ensure the stability of the battery, and can achieve excellent heat shrinkage characteristics at a thin thickness that could not be achieved by a separator using an excessive amount of an organic compound such as an organic binder.
[0068] A method for producing the separator of the present disclosure will now be described. A method for producing a separator according to the present disclosure may include the steps of producing a coating slurry containing inorganic particles and a metal silicate, and coating one or both sides of a porous substrate with the coating slurry and drying the coating slurry to form an inorganic particle layer. The porous substrate, the inorganic particle layer, the inorganic particles, and the metal silicate have been described above, and therefore detailed description thereof will be omitted.
[0069] The method for preparing the coating slurry may be any method known in the art, and is not particularly limited. According to non-limiting examples, the slurry may be prepared by dispersing inorganic particles through stirring, or agglomerated inorganic particles may be dispersed using a ball mill, a bead mill, or the like.
[0070] The coating slurry includes inorganic particles, an inorganic binder, and a solvent, and the solvent may be, but is not necessarily limited to, water, lower alcohols such as ethanol, methanol, and propanol, dimethylformamide, acetone, tetrahydrofuran, diethyl ether, methylene chloride, N-methyl-2-pyrrolidone, hexane, and cyclohexane, or a mixture thereof.
[0071] In one embodiment, the solid content of the coating slurry is not particularly limited, and may be, for example, 1 to 50% by weight, 5 to 30% by weight, or 10 to 30% by weight, but is not limited thereto.
[0072] In an embodiment, the coating slurry may further include an organic compound in an amount less than that of the inorganic binder. The organic compound has been described above, and therefore a detailed description thereof will be omitted.
[0073] In one embodiment, the metal silicate contained in the coating slurry may have a structure in which metal oxide and silica are contained at a certain molar ratio, and from the viewpoint of the coating slurry's applicability, may be a structure in which metal oxide, silica, and water are contained at a certain molar ratio. Specifically, the molar ratio of metal oxide and silica may be 1:4 to 1:10, specifically 1:4 to 1:9, more specifically 1:4.5 to 1:8.5, and even more specifically 1:5 to 1:8.
[0074] In one embodiment, the metal silicate contained in the coating slurry may be represented by the following Formula 1 or Formula 2.
[0075] [Chemical formula 1] M2O·nSiO2 In the above formula 1, M is an alkali metal, and n is 4-10.
[0076] [Chemical formula 2] MO·nSiO2·xH2O In the above Chemical Formula 2, M is an alkali metal, n is an integer of 4 to 10, and x is an integer of 50 to 150. In the above Chemical Formula 1 or Chemical Formula 2, n may be 4-9, 4.5-8.5, or 5-8.
[0077] The metal silicate satisfies Formula 1 or Formula 2, and thus the effect of connecting and fixing between the inorganic particles and between the inorganic particle layer and the porous substrate can be more effectively achieved. As a result, the separator according to an embodiment not only has more excellent binding strength between the inorganic particles and adhesion strength between the porous substrate and the inorganic particle layer, but also has excellent heat shrinkage characteristics even at a thin thickness.
[0078] The method for producing a separator according to an embodiment may further include a step of introducing a polar group to the surface of the porous substrate by hydrophilic surface treatment before the step of forming the inorganic particle layer. In this case, the polar group may be, for example, but is not limited to, a carboxylic acid group, an aldehyde group, or a hydroxyl group. In one embodiment, the hydrophilic surface treatment may include one or more of a corona discharge treatment and a plasma discharge treatment. By introducing a polar group to the surface of the porous substrate, a separator having excellent heat shrinkage properties and adhesiveness at a thin thickness can be produced.
[0079] The method of coating the coating slurry may be any method known in the art, without limitation. Non-limiting examples include roll coating, spin coating, dip coating, bar coating, die coating, slit coating, inkjet printing, and combinations thereof. The coated slurry may be dried to form an inorganic particle layer. The drying for forming the inorganic particle layer is not particularly limited, but may be performed at 100°C or lower, or at 30 to 60°C.
[0080] The present disclosure can provide an electrochemical element including a separator according to one of the above-described embodiments. The electrochemical element can have excellent thermal stability at high temperatures by including the above-described separator. In addition, the electrochemical element can have a significantly excellent life characteristic due to a reduced electrical resistance by including the above-described separator.
[0081] The electrochemical device may be any known energy storage device, but is not limited thereto, and a non-limiting example is a lithium secondary battery, which is known and has a known structure, and therefore will not be described in detail in the present disclosure.
[0082] The lithium secondary battery according to one embodiment may include the separator between the positive electrode and the negative electrode. In this case, the positive electrode and the negative electrode may be any electrode that is generally used in lithium secondary batteries.
[0083] The separator according to one embodiment, when used in a battery, is generally manufactured in accordance with a typical method in which an anode, a separator, and a cathode are arranged and assembled, and an electrolyte is injected to complete the battery, and therefore, no further detailed description will be given here.
[0084] Hereinafter, the embodiments of the present disclosure will be further described with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are merely illustrative of the present disclosure and do not limit the scope of the appended claims. It is obvious to those skilled in the art that various changes and modifications to the embodiments are possible within the scope and technical spirit of the present disclosure, and it is natural that such changes and modifications fall within the scope of the appended claims.
[0085] [Method of measuring physical properties] 1. Measurement of heat shrinkage rate (%) The separator was cut into a square with a side of 10 cm, and the transverse direction (TD) and machine direction (MD) were marked. The sample was placed in the center, five sheets of paper were placed above and below the sample, and the four sides of the paper were wrapped with tape. The sample wrapped in paper was left in a hot air drying oven at 130°C (or 150°C) for 60 minutes. The sample was then removed, the separator was measured with a camera, and the thermal shrinkage in the transverse direction was calculated using the following formula. Thermal shrinkage rate of TD (%) = ((length of TD before heating - length of TD after heating) / length of TD before heating) × 100
[0086] 2. Δ Gurley air permeability (sec / 100cc) measurement ΔGurley air permeability was measured according to ASTM D726 standard using a densometer manufactured by Toyoseiki Co., Ltd. Gurley air permeability was measured by recording the time it took for 100 cc of air to pass through a separator with an area of 1 square inch in seconds, and then calculated using the following formula. ΔGurley air permeability (sec / 100cc) = Gurley air permeability of separator with inorganic particle layer formed - Gurley air permeability of porous substrate
[0087] 3.Cardboard adhesion test The separator was cut to a size of 50 mm wide x 50 mm long and placed on the rubber pad with the inorganic particle layer facing down. A black cardboard (20 mm wide x 50 mm long x 0.25 mm thick) was placed between the separator and the rubber pad, and a constant pressure (10 g / cm) was applied using a pressing device. 2 The black cardboard was forcibly pulled out to the side, and the degree of inorganic matter adhering to the surface was checked, and the degree of adhesion was graded into A / B / C.
[0088] A: Nothing is attached. B: A small amount of inorganic matter is attached C: Level where both binder and inorganic matter are attached
[0089] 4. Measurement of the electrical characteristics of the battery Batteries were prepared using the separators of the following Examples and Comparative Examples as follows. The prepared batteries were subjected to aging and degassing operations, and then fully charged to 4.2 V, and the initial resistance (mΩ) of the batteries was measured using a J-pulse method.
[0090] Based on the total weight of the positive electrode active material, 94 wt% of LiCoO2, 2.5 wt% of polyvinylidene fluoride as a binder, and 3.5 wt% of carbon black as a conductive agent are added to NMP (N-methyl-2-pyrrolidone) as a solvent and stirred to prepare a uniform positive electrode slurry. The slurry prepared above is coated on an aluminum foil with a thickness of 30 μm, dried, and pressed to prepare a positive electrode with a total thickness of 150 μm. Based on the total weight of the negative electrode active material, 95 wt% of artificial graphite, 3 wt% of acrylic latex with a Tg of -52°C as a binder, and 2 wt% of CMC (Carboxymethyl cellulose) as a thickener are added to water as a solvent and stirred to prepare a uniform negative electrode slurry. The slurry prepared above was coated on a copper foil with a thickness of 20 μm, dried, and pressed to prepare a negative electrode with a total thickness of 150 μm. The prepared positive electrode, negative electrode, and separators of the examples and comparative examples were stacked between the positive electrode and the negative electrode to prepare a pouch-type battery. An electrolyte solution in which 1 M lithium hexafluorophosphate (LiPF6) was dissolved in a solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 30:50:20 was then injected and sealed to prepare a secondary battery with a capacity of 2 Ah.
[0091] <Example 1> Coating Slurry Production Based on the total weight of solids, 100 parts by weight of boehmite with an average particle size (D50) of 0.2 μm as inorganic particles and 1.5 parts by weight of polycarboxylate (HS-DISPERSANT 5803 manufactured by San Nopco) as a dispersant were added to distilled water and dispersed for 10 minutes using a bead mill to prepare a mixture. Next, 5 parts by weight of lithium silicate (Li2O·nSiO2, n=5) as a binder and 0.2 parts by weight of dioctyl sodium sulfosuccinate as a wetting agent were added to the mixture and stirred to prepare a coating slurry with a solids concentration of 20% by weight.
[0092] Separator manufacturing A polyethylene porous film (porosity: 42%, average thickness: 9 μm) with polar groups introduced on the surface was used as the porous substrate. Both sides of the porous film were corona discharge treated (power density 2 W / mm) to introduce surface polar groups, and the corona surface treatment was performed at a speed of 5 mpm (meter per minute). The coating slurry prepared above was applied to both sides of the porous substrate by bar coating and then dried to prepare a separator having an inorganic particle layer formed on both sides of the porous substrate with an average thickness of 1.0 μm. The physical properties of the separator are shown in Table 1 below.
[0093] <Example 2> A separator was manufactured in the same manner as in Example 1, except that the dispersant and wetting agent were used in the coating slurry in an amount of 0.7 parts by weight and 0.05 parts by weight, respectively. The physical properties of the separator are shown in Table 1 below.
[0094] <Example 3> A separator was manufactured in the same manner as in Example 1, except that sodium silicate (Na2O·nSiO2, n=5) was used as the binder instead of lithium silicate. The physical properties of the separator are shown in Table 1 below.
[0095] <Example 4> A separator was manufactured in the same manner as in Example 1, except that potassium silicate (K2O·nSiO2, n=5) was used as the binder instead of lithium silicate. The physical properties of the separator are shown in Table 1 below.
[0096] <Example 5> A separator was manufactured in the same manner as in Example 1, except that aluminum silicate (Al2O3·nSiO2, n=5) was used as the binder instead of lithium silicate. The physical properties of the separator are shown in Table 1 below.
[0097] <Example 6> A separator was manufactured in the same manner as in Example 1, except that boehmite having an average particle size (D50) of 0.6 μm was used as the inorganic particles instead of boehmite having an average particle size (D50) of 0.2 μm. The physical properties of the separator are shown in Table 1 below.
[0098] <Example 7> A separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li2O·nSiO2) with an n value of 3.5 was used as the binder instead of lithium silicate (Li2O·nSiO2) with an n value of 5. The physical properties of the separator are shown in Table 1 below.
[0099] <Example 8> A separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li2O·nSiO2) with an n value of 7 was used as the binder instead of lithium silicate (Li2O·nSiO2) with an n value of 5. The physical properties of the separator are shown in Table 1 below.
[0100] <Example 9> A separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li2O·nSiO2) with an n value of 10.5 was used as the binder instead of lithium silicate (Li2O·nSiO2) with an n value of 5. The physical properties of the separator are shown in Table 1 below.
[0101] <Example 10> A separator was manufactured in the same manner as in Example 1, except that a polyethylene porous film (porosity: 42%, average thickness: 9 μm) that was not corona discharge treated and had no polar groups introduced on the surface was used as the porous substrate. The physical properties of the separator are shown in Table 1 below.
[0102] <Comparative Example 1> Instead of lithium silicate as a binder, the glass transition temperature (T g A separator was manufactured in the same manner as in Example 1, except that 3 parts by weight of acrylic latex having a temperature of -52°C was used based on 100 parts by weight of inorganic particles. The physical properties of the separator are shown in Table 1 below.
[0103] <Comparative Example 2> A separator was manufactured in the same manner as in Example 1, except that a polyacrylamide polymer (weight average molecular weight: 300,000 g / mol) was used as a binder instead of lithium silicate in an amount of 3 parts by weight per 100 parts by weight of inorganic particles. The physical properties of the separator are shown in Table 1 below.
[0104] <Comparative Example 3> As a binder, 3 parts by weight of lithium silicate (Li2O·nSiO2, n=5) was used per 100 parts by weight of inorganic particles, and the glass transition temperature (T g A separator was manufactured in the same manner as in Example 1, except that 2 parts by weight of acrylic latex having a temperature of -52°C was used. The physical properties of the separator are shown in Table 1 below.
[0105] [Table 1]
[0106] Referring to Table 1, the separators of Examples 1 to 10 have excellent heat resistance, with a thermal shrinkage rate of less than 1% at 130°C and a thermal shrinkage rate of 7% or less at 150°C, even though they are thinner than the separators of the comparative example. In addition, an adhesion test showed that there was no or only a small amount of adhesion, indicating excellent adhesion.
[0107] In contrast, it was confirmed that the separator of Comparative Example 1 had significantly lower heat resistance and adhesive strength at a thin thickness due to the use of a particulate organic polymer as a binder, and that the separator of Comparative Example 2 had lower heat resistance at a thin thickness compared to the Examples due to the use of a water-soluble organic polymer as a binder.
[0108] In addition, it was confirmed that the separator of Comparative Example 3 contains a metal silicate according to an embodiment of the present disclosure as an inorganic binder, but contains a greater amount of all organic compounds, including dispersants, wetting agents, and organic binders, than the inorganic binder, and therefore has lower heat resistance and adhesive strength at a thin thickness than the examples.
[0109] As described above, the separator of the present disclosure can simultaneously achieve remarkably excellent heat resistance, transmittance, and adhesion by containing an inorganic particle layer that contains a metal silicate as an inorganic binder and a smaller amount of an organic compound than the inorganic binder. What has been described above is merely illustrative of the application of the principles of the present disclosure, and other configurations may be included without departing from the scope of the present disclosure.
Claims
1. A porous substrate; an inorganic particle layer located on one or both sides of the porous substrate, the inorganic particle layer including inorganic particles and an inorganic binder; A separator, wherein the inorganic particle layer contains an organic compound in an amount less than a content of the inorganic binder, and the inorganic binder contains a metal silicate.
2. The separator according to claim 1 , wherein the metal silicate connects and fixes the inorganic particles together and connects the inorganic particle layer to the porous substrate.
3. 2. The separator according to claim 1, wherein the organic compound comprises one or more first organic compounds selected from the group consisting of polycarboxylates, sulfonates, and polysiloxane-based compounds, one or more second organic compounds selected from the group consisting of ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers, and fluorine-based polymers, or a combination thereof.
4. 4. The separator of claim 3, wherein the organic compound comprises less than 30% by weight of the second organic compound, based on the total weight of the organic compound.
5. The separator according to claim 4 , wherein the organic compound does not include a second organic compound.
6. 2. The separator according to claim 1, wherein the metal of the metal silicate is any one or more metals selected from the group consisting of Group 1, Group 2, and Group 13 metals.
7. 2. The separator according to claim 1, wherein the metal of the metal silicate is any one or more metals selected from the group consisting of Group 1 and Group 2 metals.
8. The separator according to claim 7 , wherein the metal silicate is represented by the following chemical formula 1: [Chemical formula 1] M 2 O・nSiO 2 In the above formula 1, M is an alkali metal and n is 4 to 10.
9. The separator according to claim 1 , wherein the inorganic particles include any one or more selected from the group consisting of metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates.
10. The separator according to claim 1 , wherein the inorganic particles have an average particle size (D50) of 1 μm or less.
11. The separator according to claim 1 , wherein the inorganic particle layer formed on the porous substrate has a total thickness of 5 μm or less.
12. 2. The separator according to claim 1, wherein the separator has a thermal shrinkage rate of 3% or less in the width direction measured after being left at 130° C. for 60 minutes.
13. 2. The separator according to claim 1, wherein the separator has a thermal shrinkage rate of 7% or less in the width direction measured after being left at 150°C for 60 minutes.
14. 2. The separator according to claim 1, wherein the inorganic particle layer contains 0.1 to 20 parts by weight of a metal silicate with respect to 100 parts by weight of the inorganic particles.
15. The separator according to claim 1 , wherein the porous substrate comprises polar groups on a surface thereof.
16. An electrochemical element comprising the separator according to any one of claims 1 to 15.
Citation Information
Patent Citations
KR2016-0109669